In Situ and Quantitative Vapor/Solid Anion Exchange for Composition Regulation and Optical Properties of Perovskites. Issue 16 (24th May 2021) - Zhang, Zhenhua; Wei, Hao; Manohari, Arumugam Gowri; You, Daotong; Wang, Ru; Li, Zhuxin; Liu, Wei; Chen, Jinping; Zhu, Yizhi; Shi, Zengliang; Cui, Qiannan; Li, ShuZhou; et al.
Abstract: Anion exchange is a convenient postsynthetic transformation method to adjust the composition and bandgap of semiconductors. However, it is still a challenge to achieve the desired halogen‐variable perovskites due to rapid and uncontrollable reaction and difficulty to synthesize directly. Herein, a facile and gentle vapor/solid anion exchange strategy is reported to control the composition in situ and quantitatively for adjusting the properties of MAPbI3− x Br x ( x = 0 to 3, MA = CH3 NH3 ) films continuously. By controlling the reaction time, the films have a tunable bandgap from 1.58 to 2.25 eV and a continuously blue‐shifted photoluminescence peak from 771.1 to 540.5 nm. The regularly shifted X‐ray diffraction peaks reveal the successive variation in composition and crystal lattice with anion exchange and all the MAPbI3− x Br x films have a pure phase. More importantly, a universal empirical equation for in situ and quantitative composition regulation is extracted, which is supported by theoretical analysis and simulation on the anion exchange process. The anion exchange strategy and empirical equation are appropriate not only for perovskite but also for other related materials. This work may be valuable for further applications such as in situ quantitative reversible composition‐tunable perovskites, solar cells, white LEDs, and lasers. Abstract : Herein, a facile vapor/solid anion exchange strategy with in situ, continuously controllable composition and bandgap of MAPbI3– x Br x films ( x = 0 to 1) is designed. More important, an empirical equation about the quantitative relationship between the exchanged composition and the reaction time is found, which is further supported theoretically and experimentally.